Study on the Influence of Logging Cable Impedance on Transmit Current Waveform in Borehole Induced Polarization Method - MAO Yurong; GUO Qingming; XIE Xingbing; ZHOU Lei; YAN Liangjun; TONG Xiaolong; LI Haojin (Cejing jishu)
High-power induced polarization method plays an important role in deep resource exploration. During the detection process, it needs to transmit high-power excitation current through kilometers of armored cable to the well to ensure that the current waveform is not distorted so that the formation is fully polarized to achieve the purpose of detection. Therefore, it is very important to study the impedance characteristics of kilometer-level armored cables weighing tons for deep resource exploration. After establishing the high frequency model and low frequency model of the kilometer-level cable, the distribution parameters of the cable are deduced, and the 3 000meter logging cable is tested and analyzed by impedance analyzer and field test. The results show that the cable has different effects on the magnitude and waveform of the transmitted current, the signal phase, the amplitude-frequency characteristics and phase-frequency characteristics of the cable in different frequency bands. In the case of long line transmission in the well, the impedance characteristics of kilometer-grade armored cable should be paid special attention in the preliminary design of the well detection system, and the impedance matching should be considered to achieve effective detection.